2014
DOI: 10.3233/nib-140079
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity Post-Hematopoietic Stem Cell Transplantation: Focus on Epigenetics

Abstract: Epigenetic regulation of gene expression is important for normal biological processes like immune cell development, immune responses, and differentiation from hematopoietic stem cells. Furthermore, it is well understood that epigenetic mechanisms can include methylation, histone modification, and more recently, microRNAs. Interestingly, aberrant epigenetic modification can also promote pathology in many diseases like cancer. The effects of methylation on gene expression and its resulting phenotype have been ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…[75] Immune reconstitution following allogeneic HSC transplantation occurs in several phases. [76] An early phase of rapid myeloid cell reconstitution occurs within 20-30 days, while lymphoid cell reconstitution is delayed by up to a year. [77] Patients experience an "aplastic phase" of severe neutropenia until neutrophil progeny appear.…”
Section: Protocols Used In Human Hsc Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…[75] Immune reconstitution following allogeneic HSC transplantation occurs in several phases. [76] An early phase of rapid myeloid cell reconstitution occurs within 20-30 days, while lymphoid cell reconstitution is delayed by up to a year. [77] Patients experience an "aplastic phase" of severe neutropenia until neutrophil progeny appear.…”
Section: Protocols Used In Human Hsc Transplantationmentioning
confidence: 99%
“…Immune reconstitution following allogeneic HSC transplantation occurs in several phases . An early phase of rapid myeloid cell reconstitution occurs within 20–30 days, while lymphoid cell reconstitution is delayed by up to a year .…”
Section: Protocols Used In Human Hsc Transplantationmentioning
confidence: 99%
“…There have been other studies that have also found a functional defect in monocytes after allogeneic HSCT, 31,32 and epigenetic changes in the regulation of the innate immune system have been suggested as a potential cause. 33 In our study, the infected HSCT patients did have a lower monocyte count than uninfected HSCT patients, which could have contributed to increased susceptibility to viral infections. However, our gene expression analysis used purified monocytes, which would have normalized the difference in monocyte count between infected and uninfected HSCT patients.…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, we noted higher levels of IL-1β in BMDMs pre-treated with PGE 2 and infected with methicillin-resistant Staphylococcus aureus (MRSA) or Streptococcus pneumoniae compared to infected BMDMs not treated with PGE 2 ( Supplemental Fig.2B ). MRSA and S.pneumoniae are also main pathogens that infect immunosuppressed individuals 6 , 19 , 31 , 32 .…”
Section: Resultsmentioning
confidence: 99%
“…P. aeruginosa is an opportunistic pathogen which causes minimal pathogenicity in healthy individuals, but major mortality and morbidity in HSCT patients 2 , 6 , 19 , 31 , 37 , 38 . Susceptibility to this pathogen has been reported to occur even after immune reconstitution following HSCT 2 , 6 , 31 . HSCT patients have high levels of PGE 2 in the blood and BALF when compared to healthy individuals 18 - 20 .…”
Section: Discussionmentioning
confidence: 99%